130k views
3 votes
Y = -x + 5
y = -2x + 4

User Axle Max
by
5.0k points

1 Answer

2 votes

Answer:

x = -1

Explanation:

To solve this we have to make the equations equal to each other;

-x + 5 = -2x + 4

Add 2x to both sides

1x + 5 = 4

Subtract 5 from both sides

1x = -1

Divide both sides by 1

1x = -1 OR x = -1

Then you plug in the value of x to get the value of y; Just pick one of the equations.

y = -x + 5

Let's plug in the value of x;

y = -(-1) + 5

y = 1 + 5

y = 6

(x, y) = (-1, 6)

User John Rees
by
4.5k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.